Graphene material prepared by thermal reduction of the electrochemically synthesized graphite oxide. Issue 67 (1st July 2016) - Gurzęda, B.; Florczak, P.; Wiesner, M.; Kempiński, M.; Jurga, S.; Krawczyk, P.
Abstract : The present work describes a simple and effective way to produce bulk quantities of graphene material. Abstract : In the present work we demonstrate a simple and effective way to produce bulk quantities of graphene material. For the first time, graphite oxide (GO), synthesized by electrochemical treatment of natural graphite in HClO4 aqueous solution, was used to obtain thermally exfoliated-reduced graphite oxide (TRGO). Herein, GO was thermally exfoliated and reduced at 500 °C in air, giving the final product of TRGO. Due to shock treatment, the volume of the synthesized TRGO drastically increased compared to the starting GO. Furthermore, the exfoliation process resulted in a significant decrease in the concentration of oxygen functionalities. The choice of GO exfoliation temperature was preceded by thermogravimetric analysis (TGA). TRGO was characterized using X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and atomic force microscopy (AFM) analysis.